PENGARUH PERAN ISLAMIC CORPORATE GOVERNANCE DAN KUALITAS AUDIT TERHADAP MANAJEMEN LABA - Herni Aprillia Aeni; Saskia Jamilah Khairany; Titin Vegirawati (Program Studi Perbankan Syariah, 2020)
This study aims to determine and empirically examine the effect of Islamic corporate governance and audit quality on earnings management. The type of research used is quantitative using secondary data in the form of data from the financial statements of Islamic banks listed on the OJK website from 2015 to 2019. The sampling method in this study uses purposive sampling with a sample of 13 Islamic banks in Indonesia with a 5 years period. research. This study uses a panel data regression test. In this study, earnings management is measured using discretionary accruals. The results show that the percentage of the influence of Islamic corporate governance and audit quality on earnings management is 15.41%. The t test results indicate that the Islamic corporate governance variable has no significant effect on earnings management and audit quality has a positive effect on earnings management.